COMPARATIVE ANALYSIS OF TAYLOR SWIFT FAN (SWIFTIES) ACTIVITY ON SOCIAL MEDIA - Fariza, Muhammad Rio; Sofyan, Khoridho Abdillah (SOURCE : Jurnal Ilmu Komunikasi, 2025)
Taylor Swift is a multi-talented singer-songwriter and global superstar who has captivated audiences with heartfelt lyrics and catchy melodies that have attracted fans worldwide, including Indonesia. This study aims to explore and compare the activities of the Indonesian Taylor Swift fan community (Swifties) on social media. With a qualitative approach and content analysis methods, this study examines the interaction of Swifties on social media platforms such as X, Instagram, and TikTok. The data was collected from Swifties Indonesia's social media accounts, which have the most followers on each platform. The results showed that Swifties Indonesia showed a high level of interaction and participated in various activities, including promoting Taylor Swift's work, social campaigns, and fundraising. Swifties took to social media to share content related to Taylor Swift, creating a sense of community and solidarity among fans.